Political Trust and Russian Media in Latvia - Berzina Ieva (Journal on Baltic Security, 2018)
Russia’s attempts to influence public opinion outside its borders attracted increased interest in the context of its involvement in the war in Ukraine, Brexit referendum, the elections in the US and other political processes in the West. This article focuses on the assumption that Russian activities in the information environment of NATO and the EU member states among other things are aimed at undermining public trust in democratic governance institutions. Russian state-owned media is one of the tools about how Kremlin disseminates and promotes its worldview within and outside Russia’s borders; therefore, the research questions being addressed in this paper are related to the relationship between political trust and consumption of Russian media. To study this issue, Latvia was chosen as an outstanding case due to the relatively large presence of Russian media content in its information environment. The paper examines the trends of Russian media consumption and political trust in Latvia to assess if this is a fruitful further research area since linking political trust and Russia’s information activities is a new perspective on the issue. The theoretical part of the paper outlines the concept of political trust and the factors affecting it as they are identified in previous research, with a specific focus on the impact of media on political trust. The empirical part of the paper examines the trends in the growth of the audience of the TV channels retranslating Russian media content and political trust in Latvia in the period from 2007 to 2017. Considering that political trust in Latvia is increasing alongside with an increase in Russian media consumption, this paper suggests several further research directions with a focus on political and economic performance indicators and the impact of domestic media.